Guiding the Seafarers: The South African Hydrographic Office and the Contribution of the Three Proteas - Potgieter, Thean (Scientia Militaria - South African Journal of Military Studies, 2013)
As seafarers require a comprehensive record that provides information on coastlines, the seabed and sea conditions, cartography dates back to antiquity.  During the early modern period, states and merchant companies employed cartographers to collect and report important nautical information.  The Dutch East India Company (VOC), for example, created valuable nautical charts and provided detailed sailing instructions on the South African coast.  Open exchange of such information is a twentieth-century phenomenon dating back to the creation of the International Hydrographic Organisation (IHO) in 1921.  The SA Navy was created in 1922.  One of its first ships was the survey ship HMSAS Protea, which was laid up in 1933.  During the two decades following the Second World War, hydrographic survey work was done by three converted former Royal Navy vessels (SAS Protea, SAS Natal and SAS Haerlem).  South Africa became a member of the International Hydrographic Organisation (IHO) in 1951 and the SA Navy established its own Hydrographic Office in April 1955.  The SA Navy’s Hydrographic vessels were always outdated or redundant ships, but in 1972 the SA Navy commissioned its first purpose-built hydrographic survey ship (the current SAS Protea).